2008
DOI: 10.1021/jm800277g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of (−)- and (+)-Debromoflustramine B and Its Analogues as Selective Butyrylcholinesterase Inhibitors

Abstract: A series of pyrrolidinoindolines have been synthesized as debromoflustramine B (4a) analogues for their evaluation as cholinesterase inhibitors. Structure-activity studies of this series revealed the optimum pharmacophoric elements required for activity and resulted in the discovery of selective butyrylcholinesterase inhibitors with micromolar potency. Biological testing demonstrated that (-)-4a was 7500 times more potent than its enantiomer (+)-4b. The most active inhibitor against BChE in the series was deme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…It also showed potent inhibitory activity against AChE with the IC 50 value of 2.61 ± 0.13 μM. This result was similar to the Rivera-Becerril’s report [38], confirming the double bond of the prenyl group is interacting as a specific π-hydrogen bond acceptor with the enzyme. The influence order is prenylated oxyl > allyloxy > methoxyl > hydroxyl.…”
Section: Resultssupporting
confidence: 89%
“…It also showed potent inhibitory activity against AChE with the IC 50 value of 2.61 ± 0.13 μM. This result was similar to the Rivera-Becerril’s report [38], confirming the double bond of the prenyl group is interacting as a specific π-hydrogen bond acceptor with the enzyme. The influence order is prenylated oxyl > allyloxy > methoxyl > hydroxyl.…”
Section: Resultssupporting
confidence: 89%
“…The flustraminef amily comprises over 20 prenylated indole al- [19] whereas debromoflustramine Ba nd its analogues have been evaluated for their butyrylcholinesterase inhibitory activity: (À)-debromoflustramine Bi so ver 7500times more potent than its (+ +)-enantiomer. [20] Amides 13 and 22 were previously reported as intermediates in the total syntheses of flustramides A [21] and B [22] and flustramines Aa nd B. [23] Reductive cyclization with alane-dimethylethylamine complex (Scheme 6) was carriedo ut on (+ +)-13 (prepared using (R,R)-L 2 )a nd (+ +)-22 (prepared using (S,S)-L 1 )t o obtain the unnatural (+ +)-isomers of all four natural products, spectrald ata of which was in agreement with literature reports.…”
Section: Total Syntheses Of Flustra Alkaloids and Determination Of Thmentioning
confidence: 99%
“…[17][18][19][20] It is suggested that BuChE is a key player in brain areas that influence the aggregation of neuritic Aβ plaques due to the correlation between BuChE polymorphisms and the progression of cognitive impairment in dementia with Lewy bodies (DLB) and AD. [21][22][23] It is also believed that BuChE is particularly important in individuals with more severe dementia, since its activity is increased with disease development. Therefore, compounds that can interact specifically with PAS or CAS residues are important in ChE inhibition and may help in prevention of Aβ aggregation facilitated by AChE.…”
mentioning
confidence: 99%